2019
DOI: 10.28991/cej-2019-03091317
|View full text |Cite
|
Sign up to set email alerts
|

Green Envelop Impact on Reducing Air Temperature and Enhancing Outdoor Thermal Comfort in Arid Climates

Abstract: Today Urban Cities faces energy and environmental challenges due to increased population, higher urbanization. The building sector has a big responsibility as it acquires high consumption rates in global energy and environmental scenarios. It is thought that the built environment in Egypt is responsible for 26% of the total overall national energy consumption, 62% of the total electricity consumption and around 70% of resultant CO2 emissions. The increased use of electrical appliances causes Urban Heat Island … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…4) Socio economic drought: In which drought causes economic and social negative effects on people's lives. For example, farmers' income decreases [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…4) Socio economic drought: In which drought causes economic and social negative effects on people's lives. For example, farmers' income decreases [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The measurements taken to reduce energy consumption in residential building should not affect thermal comfort conditions. Some authors have suggested and studied the effect of facade shading and green roofs in conserving thermal comfort with less consumed energy [14][15][16]. These different modeling techniques have different strengths, weaknesses, capabilities, and applicabilities.…”
Section: Overview Of Modeling Methodologiesmentioning
confidence: 99%
“…is effectively solving above issue [24][25][26]. In addition, some new technologies are used to solve problems of energy consumption (such as technology of green envelop, driving technologies) [27,28].…”
Section: Author Copymentioning
confidence: 99%